Consumer Protection for High School Students with Disabilities: Between Practice and Context - Anna Maria Tri Anggraini; Ahmad Sabirin; Muhammad Firli Israriyanto; Sharda Abrianti (Journal of Consumer Sciences, 2025)
Background: In fact, there are still many students with disabilities who do not get their rights in schools with adequate facilities and infrastructure. Purpose: This study examines how consumer protection efforts are carried out by four (4) high schools in North Bekasi District based on Bekasi Regional Regulation Number 16 of 2019 concerning the Protection and Fulfilment of the Rights of Persons with Disabilities and Consumer Protection Obstacles faced by four high schools in North Bekasi District based on Bekasi Regional Regulation Number 16 of 2019. Methods: This research is normative, based on secondary and primary data gathered through direct interviews with the authorities in four (4) high schools in Bekasi. Findings: The interesting findings are that consumer protection efforts to protect and fulfill the rights of persons with disabilities are still not fully implemented. Related, the fulfillment of the right to inclusive education has been fully implemented but is inversely proportional to the implementation of accessibility. The obstacles faced in realizing consumer protection for students with disabilities are in fulfilling accessibility, both non-physical and physical accessibility. Conclusions: This study shows that although consumer protection efforts to fulfill the rights of persons with disabilities in four high schools in North Bekasi District have been carried out, their implementations are still not fully effective, especially for accessibility. Although the right to inclusive education has been fulfilled, significant challenges remain in ensuring adequate physical and non-physical accessibility. Research implication: The study is expected to provide input to the local government of Bekasi and other local governments on paying attention to the rights of people with disabilities in schools, both facilities and pre-facilities, to provide comfort and the rights of citizens as mandated in the constitution of justice for the entire nation of Indonesia.